2018
DOI: 10.1038/s41598-018-24947-2
|View full text |Cite
|
Sign up to set email alerts
|

Low field magneto-tunable photocurrent in CoFe2O4 nanostructure films for enhanced photoelectrochemical properties

Abstract: Efficient solar to hydrogen conversion using photoelectrochemical (PEC) process requires semiconducting photoelectrodes with advanced functionalities, while exhibiting high optical absorption and charge transport properties. Herein, we demonstrate magneto-tunable photocurrent in CoFe2O4 nanostructure film under low applied magnetic fields for efficient PEC properties. Photocurrent is enhanced from ~1.55 mA/cm2 to ~3.47 mA/cm2 upon the application of external magnetic field of 600 Oe leading to ~123% enhancemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…CoFe 2 O 4 crystallizes in a mixed spinel phase. , An ideal inverse spinel can be described as [B 3+ ] tet [A 2+ B 3+ ] oct O 4 . The T 2g (2) Raman mode can be assigned to Co 2+ at the octahedral site, while the A 1g‑sub Raman mode corresponds to Co 2+ on the tetrahedral site. ,, The strong increase in intensity of the T 2g (2) Raman mode with increasing Fe content indicates that more Co 2+ ions are located at the octahedral sites. Thus, the spinel structure becomes more inverse.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CoFe 2 O 4 crystallizes in a mixed spinel phase. , An ideal inverse spinel can be described as [B 3+ ] tet [A 2+ B 3+ ] oct O 4 . The T 2g (2) Raman mode can be assigned to Co 2+ at the octahedral site, while the A 1g‑sub Raman mode corresponds to Co 2+ on the tetrahedral site. ,, The strong increase in intensity of the T 2g (2) Raman mode with increasing Fe content indicates that more Co 2+ ions are located at the octahedral sites. Thus, the spinel structure becomes more inverse.…”
Section: Resultsmentioning
confidence: 99%
“…In order to access structural properties, defect states, and surface adsorbates, optical spectroscopy is a powerful tool. While there are various reports on structural properties of Co 3 O 4 and CoFe 2 O 4 , extracted via Raman spectroscopy, only a few consider different Co/Fe ratios in Co x Fe 3– x O 4 . Nakagomi et al investigated Fe-rich Co x Fe 3– x O 4 nanoparticles ( x = 0.05 to 1.6), observing a hematite secondary phase for x ≤ 0.4. Bahlawane et al and Yan et al showed for Co x Fe 3– x O 4 thin films ( x = 1.44 to 3 and x = 1.29 to 2.55), an A 1g Raman mode broadening and a shift to lower wave numbers with increasing Fe content, which is explained by the substitution of Co cations with Fe 3+ ions on the octahedral site.…”
Section: Introductionmentioning
confidence: 99%
“…CoFe 2 O 4 (CFO) is a unique member of the magnetic ferrites having a wide variety of interesting properties, such as large magnetic anisotropy, a large coercive field, a large magnetostriction coefficient, moderate saturation magnetization, superparamagnetism, tunable photomagnetism, and an optical band gap in the visible light region, making it a versatile candidate for numerous potential applications. For instance, the superparamagnetism and highly active catalytic performance exhibited in crystalline CFO nanoparticles have promised their unique application potentials in medical and environmental emission control, respectively. In particular, the physical properties of the CFO nanoparticles can be further modified and controlled by their sizes, shapes, and chemical compositions. CFO nanoparticles could also be combined with other materials as nanocomposites having core–shell structures to enhance their functionality .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the physical properties of the CFO nanoparticles can be further modified and controlled by their sizes, shapes, and chemical compositions. CFO nanoparticles could also be combined with other materials as nanocomposites having core–shell structures to enhance their functionality . On the other hand, the CFO thin films have also exhibited a broad range of magnetic, optical, and electrical properties suitable for integrating a wide variety of spintronic and opto-magnetic devices. Perhaps one of the advantages of CFO thin films is their physical property tunability via strain engineering by choosing appropriate substrates and controlling the growth parameters. Examples of manipulating the magnetic anisotropy and the optical band gap of CFO films by controlling the film thickness with deliberately selected substrates have been demonstrated previously. …”
Section: Introductionmentioning
confidence: 99%
“…The magnetic field tunable photocurrent has also been observed in the CoFe 2 O 4 based nanostructure thin film. 30 Sheng et al have studied the magnetic field tunable photocurrent in La 0.7 Sr 0.3 MnO 3 /SrTiO 3 based p−n junction. 31 In all of the above cases, ferroelectric and ferromagnetic materials are explored for photovoltaic applications by leveraging either their ferroelectric or their ferromagnetic properties independently.…”
Section: ■ Introductionmentioning
confidence: 99%